Cemaran Kapang pada Pakan Sapi dan Uji In Vitro Sirih terhadap Pertumbuhan Kapang Aspergillus flavus (MOLD CONTAMINATION IN CATTLE FEED AND IN VITRO ASSAY OF PIPER BETEL AGAINTS GROWTH OF MOLD CONTAMINANT ASPERGILLUS FLAVUS ) - Ahmad, Riza Zainuddin; Gholib, Djaenudin (Jurnal Veteriner, 2017)
Contamination of mold in feed and Ingridients of feed is important because pathogenic and toxigenic mold will contaminate and cause mycotic and mycotoxicosis on livestock especially cattle. Information regarding the data is required in an attempt to controll of mold contaminant. Base on the previous study piper betel leaf ( Piper betle) showed high activity as antimold. The aim of this study were to obtain data of mold contamination in cattle feed and ingredients of feed from the provinces of Banten, Lampung, Jakarta and West Java, and to test piper betel as an antimold herbal from traditional medicinal plants originated from Indonesia. Isolation and identification of fungi were conducted on the flour, glycerides, onggok, corn, peanut, coconut, coffee, concentrates, lamtoro, pineapple, rice, grass, palm, cassava, tofu lees, fish meal, bone meal from the provinces of Banten, Lampung, Jakarta and West Java. Isolation was done by plating the samples on agar medium, The mold have grown on media was identified. Feed that has been mixed with the extracts and powders plus mold inoculum was incubated. After 3=7 days incubation, colony forming unit (CFU) of the mixtures were counted. The results showed that the majority of feed contaminated with mold, but still below the threshold. The mold contamination in wheat flour, corn, concentrates and tofu lees exceeds from the threshold. Aspergillus sp, A. amstelodami, A. clavatus, A. Candidus, A. flavus, A. fumigatus, A. glaucus, A. niger, Cladosporium sp., Curvularia sp., Fusarium sp., Hyphomycetes sp., Mycelia sterilata, Mucor sp., Paecilomyces sp., Penicillium sp., and Rhizopus sp. Penicillium sp were most commonly found in the feed as much as 2.56 x 107 CFU. At a concentration of 10%. in vitro test showed that the piper betel leaf in powder form is more effective than extract form to inhibit the growth of A.flavus The conclusion of this study was flour, corn, concentrates and tofu lees contaminated by molds. Penicillium sp and 17 species of mold were the most frequently found compared to other fungi. Powders the best form of the piper betel as antimold. ABSTRAK Cemaran kapang pada pakan dan bahan penyusunnya adalah penting sebab kapang yang tergolong patogenik dan toksigenik dapat mencemari dan menyebabkan mikosis dan mikotoksikosis pada ternak sapi. Informasi mengenai kapang pencemar diperlukan dalam usaha pengendaliannya. Berdasarkan penelitian sebelumnya diketahui daun sirih ( Piper betle ) mempunyai aktivitas antikapang yang tinggi . Penelitian ini bertujuan untuk memperoleh data cemaran kapang pada pakan ternak sapi dan bahan penyusunnya dari propinsi Banten, Lampung, DKI Jakarta, dan Jawa Barat, serta menguji sirih sebagai obat herbal antikapang yang telah terpilih dari tanaman obat tradisional asli Indonesia. Isolasi dan  identifikasi kapang telah dilakukan pada tepung, gliserida, onggok, jagung, kacang, kelapa, kopi, konsentrat, lamtoro, nenas, beras, rumput, sawit, singkong, ampas tahu, tepung ikan, tepung tulang dari provinsi Banten, Lampung, DKI Jakarta, dan Jawa Barat. Isolasi dilakukan dengan membiakkan sampel pada media agar, Kapang yang sudah tumbuh pada media diidentifikasi. Pakan yang telah dicampur dengan ektrak dan serbuk ditambahkan inokulum kapang, kemudian diinkubasi. Setelah 3-7 hari diinkubasi, dihitung colony forming unit (CFU) yang berkembang. Hasil penelitian menunjukkan bahwa sebagian besar pakan tercemar kapang, tetapi levelnya masih berada di bawah batas ambang. Cemaran kapang pada tepung, jagung, konsentrat, dan ampas tahu melebihi batas ambang. Kapang-kapang tersebut adalah Aspergillus sp, A. amstelodami, A. clavatus, A. candidus, A. flavus, A. fumigatus, A. glaucus, A. niger, Cladosporium sp., Curvularia sp., Fusarium sp., Hyphomycetes sp., Miselia sterilata, Mucor sp., Paecilomyces sp., Penicillium sp., dan Rhizopus sp. Kapang Penicillium sp adalah yang paling banyak ditemukan pada pakan yakni sebanyak 2,56.107 CFU. Uji in vitro menunjukkan bahwa daun sirih dalam bentuk serbuk lebih efektif dibandingkan bentuk ekstrak untuk menghambat pertumbuhan A. flavus pada konsentrasi 10%. Simpulan penelitian ini adalah tepung, jagung, konsentrat dan ampas tahu tercemar oleh kapang. Ditemukan 17 jenis kapang pencemar pakan dan kapang Penicillium sp yang paling banyak jumlahnya. Antikapang sirih yang terbaik adalah dalam bentuk serbuk.